The mediating influence of national culture on the relationship between job happiness and job satisfaction in Dubai Metro - Khalfan Aldahmani, Ahmed Khamis Obaid (2022)
The discourse on job happiness and job satisfaction is much available from Western and Eastern countries, but it is still limited in the Middle East. In order to determine and increase the job satisfaction among its employees, management must ensure effective job happiness. Despite this, only few research has examined the relationship between job happiness and job satisfaction among United Arab Emirates government employees. This study examined the effects of job happiness and national culture on job satisfaction among UAE government employees. A quantitative research approach along with a cross-sectional research design has been used to collect data from 357 UAE government employees in the target population through a self-administered questionnaire. This research used a mixed approach in both surveys and interviews to gather data. The analysis was conducted using quantitative and qualitative tools to recognize the gaps and the factors that influence happiness at work. Next, this work provided recommendations to raise job happiness across organizations over the long run. This study’s findings emphasize the necessity of correlating national practices, culture, and systems with strategic planning that focuses on employee happiness to improve an organization. The findings emphasize the power of two factors related to boosting employees’ positive feelings towards work: leadership style and national culture. The findings also showed that the role of religion in raising happiness, in general, is more precise than its role in increasing happiness at work. Employees from the sample group, who are strongly practicing religious rituals, still show a shallow sense of work regardless of all the facilities they are given to practice their religion